2015
DOI: 10.1088/0268-1242/30/9/094008
|View full text |Cite
|
Sign up to set email alerts
|

Properties of hybrid MOVPE/MBE grown GaAsBi/GaAs based near-infrared emitting quantum well lasers

Abstract: A combined growth approach involving both molecular-beam epitaxy and metal-organic vapor phase epitaxy has been developed to fabricate GaAsBi/GaAs-based quantum well (QW) laser structures with a Bi composition up to 8%. Lasing operation has been demonstrated at room temperature at 1.06 μm in laser diodes containing 3QWs that in turn contain approximately 6% Bi. A 5QW device demonstrated lasing at 1.09 μm at 80 K. Using temperature-and pressuredependent measurements of stimulated emission as well as pure sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…Although Moussa et al reported that the PL intensity of GaAsBi enhances about one order of magnitude with an annealing temperature of about 700 • C [148], they suggested that the PL intensity improvement is dominated by the reduction of non-Bi-related defects [145]. Nevertheless, GaAsBi laser diodes [248,249] and LEDs [250] have been realized, suggesting the promising application of dilute bismides on optoelectronic devices.…”
Section: Photoluminescence Intensitymentioning
confidence: 99%
“…Although Moussa et al reported that the PL intensity of GaAsBi enhances about one order of magnitude with an annealing temperature of about 700 • C [148], they suggested that the PL intensity improvement is dominated by the reduction of non-Bi-related defects [145]. Nevertheless, GaAsBi laser diodes [248,249] and LEDs [250] have been realized, suggesting the promising application of dilute bismides on optoelectronic devices.…”
Section: Photoluminescence Intensitymentioning
confidence: 99%
“…13 These defect-related issues have become a bottleneck in the successful applications of GaAsBi. For instance, to date, GaAsBi-based laser diodes require a threshold current density (2-10 kA cm − 2 ) 6,[14][15][16] that is approximately an order of magnitude higher than that of typical InGaAs-based laser diodes (0.2-0.5 kA cm − 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by reabsorption effect when photons propagate along the device structure. 3 The FWHM of PL broadens to 124 meV at RT, which further proves the inhomogeneous broadening of the active layer. This inhomogeneous broadening effect has been observed for quantum dot lasers, which are representative examples of intensely inhomogeneous devices.…”
Section: Fig 2 Depicts Both Voltage-current (V-imentioning
confidence: 79%
“…The threshold current (I th ) is 435 mA, giving a threshold current density (J th ) of 4.54 kA/cm 2 . Compared with the 1060 nm lasers grown jointly by MBE and MOVPE (J th =25 kA/cm 2 ), 3 the threshold current density is significantly reduced. This could be attributed mainly to the optimization of MBE growth, which effectively suppresses impurities and defects and reduces the non-radiative recombination center.…”
Section: Fig 2 Depicts Both Voltage-current (V-imentioning
confidence: 96%
See 1 more Smart Citation